Criteria for assessing the speed of movement in young men in rowing on kayaks - Bogush, V.; Getmantsev, S.; Bogatyirev, K.; Koloskova, I.; Sokol, O.; Reznichenko, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to develop quantitative criteria for assessing the physical quality of the speed and its constituent elements for modeling the training process in rowing on kayaks.